Depression and smoking: mediating role of vagal tone and inflammation - Taylor, Laine; Loerbroks, Adrian; Herr, Raphael; Lane, Richard D.; Fischer, Joachim E. (Annals of behavioral medicine, 2011)
Depressed adults are more likely to become nicotine dependent and smokers are at increased risk for depression. Smoking and depression are each associated with inflammation and vagal tone.The purpose of this study is to determine as to what extent the association between depression and smoking is mediated by inflammation and/or vagal tone.We studied a cross-sectional occupational sample (n = 647) with information on the number of cigarettes smoked per day and depression (as measured by the Hospital Anxiety and Depression Scale). Heart rate variability, an indicator of vagal tone, was measured by electrocardiographic recordings. Inflammatory markers included C-reactive protein, white blood cells, and fibrinogen. Linear regression was employed along with the Freedman-Schatzkin test to assess mediation.We observed a positive association between depression and smoking (p < 0.05). Vagal tone and fibrinogen were found to weakly attenuate this association.These are the first data to demonstrate that the association between depression and smoking may partially be mediated by vagal tone and fibrinogen.
Gesehen am 26.10.2022